Detection of explosives - Dovbnya, A.N.; Yegorov, A.M.; Zhuk, V.V.; Pugachev, G.D.; Shapoval, I.I.; Shepelev, A.G. (Вопросы атомной науки и техники, 2006)
The extensive literature on the methods of detection of explosives under the stationary and field conditions is reviewed. Today, there are hundreds of publications on detectability of explosives by different methods, but none of the methods gives a 100% guarantee of explosives detection. Consideration has been given to advanced high-technology methods of explosives detection: nuclear quadrupole resonance method, nuclear physics methods (slow and fast neutrons, gamma-quanta), biological methods. Notice that the danger of newly created explosives, including land mines, increases. The actuation systems are also constantly improved. Most difficulties with detection, extraction and deactivation of explosive devices can be overcome with the help of updated methods and techniques. The present review calls attention primarily to the possibility of solving the pressing and complicated problems using charged particle accelerators.